Partisipasi Anggaran dan Kinerja Managerial di Pemerintah Daerah: Anteseden dan Pemediasi - Nur Laila Yuliani; Barkah Susanto (Journal of Accounting and Investment, 2018)
Budget participation has an important role especially in the local government. A higher motivation and commitment will created through budget participation in order improving performance. This study uses a structural equation modeling approach to investigate the influence of information asymmetry and leader member exchange on budget participation to managerial performance by using goal commitment and ambiguity role as mediation variables, in Working Units, Magelang Municipality Government, Central Java. Based on a questionnaire survey of 101 local government officials involved in budget preparation, we find that information asymmetry has a positive effect on budget participation. The commitment on goals mediates the relationship between budget participation and managerial performance. Otherwise budget participation has no effect on managerial performance through role ambiguity. This study also find that leader member exchange has no effect on budget participation.